1997
DOI: 10.1007/bf01212609
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of matrilysin expression in cells of squamous cell carcinoma by E-cadherin-mediated cell-cell contact

Abstract: A critical attribute of invasive carcinomas is their ability to degrade components of the extracellular matrix, a process achieved by the matrix metalloproteases. In the human squamous cell carcinoma cell line II-4, mRNA and protein expression of the matrix metalloprotease matrilysin was observed to be significantly higher in confluent than in log-phase growth conditions. The purpose of this study was to determine the basis for this switch in constitutive matrilysin expression. Conditioned medium from confluen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Another level of regulation is that total proteinase activity is modulated by specific tissue inhibitors of metalloproteinases (TIMPs), which complex with MMPs and keep them in an inactive state. MMPs are regulated at the transcriptional level by growth factors, tumor promoters, oncogenes, and adhesion molecules [34,35]. The coordinated induction of several MMPs by these agents is due to the similarity in the 5' flanking region of their promoters.…”
Section: Discussionmentioning
confidence: 99%
“…Another level of regulation is that total proteinase activity is modulated by specific tissue inhibitors of metalloproteinases (TIMPs), which complex with MMPs and keep them in an inactive state. MMPs are regulated at the transcriptional level by growth factors, tumor promoters, oncogenes, and adhesion molecules [34,35]. The coordinated induction of several MMPs by these agents is due to the similarity in the 5' flanking region of their promoters.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of E-cadherin expression in a transgenic mouse model of pancreatic ␤-cell carcinogenesis (Rip1Tag2) coincides with the transition from well-differentiated adenoma to invasive carcinoma (92). Curiously, it has also been demonstrated that E-cadherin stimulates expression of MMP-7 through the wnt-signaling pathway (93).…”
Section: Discussionmentioning
confidence: 99%
“…In most carcinomas, MMPs are expressed in stromal cells and many have been shown to be regulated by interaction with ECM through integrins (Pilcher et al, 1997;Damsky et al, 1997). In contrast, matrilysin expression is found at high levels in well-dierentiated epithelial cells (Wilson and Matrisian, 1998) and has been shown to be tightly regulated by E-cadherin mediated cell/cell contact (Borchers et al, 1997). Thus, the expression pattern of these enzymes are at least partly controlled by the particular extracellular environment, even as the enzymes themselves are capable of altering this environment.…”
Section: Discussionmentioning
confidence: 99%